2022
DOI: 10.3390/ijerph19041919
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure Care: Testing Dyadic Dynamics Using the Actor-Partner Interdependence Model (APIM)—A Scoping Review

Abstract: Self-care behaviors are essential for the effective treatment of heart failure (HF), and poor self-care may lead to adverse clinical events in patients with HF. A growing body of literature addresses the need to analyze the characteristics of both patient and caregiver since they are in mutual, long-term interaction, and their reactions to events are dependent on each other. One of the most common approaches for analyzing data on HF self-care dyads is the Actor–Partner Interdependence Model (APIM). The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
(113 reference statements)
1
4
0
Order By: Relevance
“…In line with previous studies, 10,52 our study showed that both patients' self-care management and caregivers' contributions to self-care management were inadequate, indicating the challenge of implementing HF self-care management for both patients and caregivers. Considering both the significance and inadequacy of self-care management, our findings may provide new paths for developing interventions to improve HF self-care management.…”
Section: Discussionsupporting
confidence: 90%
“…In line with previous studies, 10,52 our study showed that both patients' self-care management and caregivers' contributions to self-care management were inadequate, indicating the challenge of implementing HF self-care management for both patients and caregivers. Considering both the significance and inadequacy of self-care management, our findings may provide new paths for developing interventions to improve HF self-care management.…”
Section: Discussionsupporting
confidence: 90%
“…Both social participation and close family relationships are important ways to boost social support. It’s worth noting that a distinctive feature of the dyadic approach to patient care is the focus on dyadic health ( Uchmanowicz et al, 2022 ), rather than the individual patient or caregiver.…”
Section: Discussionmentioning
confidence: 99%
“…The MSPSS has twelve items that measure the perceived adequacy of the available amount of SS. The amount of SS is rated on a 7-point Likert scale with responses ranging from very strongly disagree (1) to agree (7) very strongly. The total is calculated through the sum across all the items then divided by 12, with higher scores indicating higher perceived social support.…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…A recent review about dyadic dynamics in HF showed the interrelationship of patient and caregiver and highlighted the need to include both care partners [7]. Despite caregivers play a pivotal role in the recovery of their relatives with HF, supporting them in promoting health and symptom management is challenging.…”
Section: Introductionmentioning
confidence: 99%